Attendance System of Computer Laboratory Assistant in PT.XYZ Using Wireless Fidelity - Rahmat Sulaiman; Agustina Mardeka Raya; Tri Sugihartono; Fransiskus Panca Juniawan; Ayu Ratna Juwita (Universitas Raharja, 2022)
The use of Android smartphones is becoming increasingly widespread in all walks of life in people's daily lives. Supported by the development of mobile applications that are so innovative and varied, is one of the reasons. Mobile application development aims to support almost all human activities, especially in the world of work, therefore the programmer creates a presence system using Android-based wireless fidelity (WIFI) at laboratory of PT.XYZ. At the laboratory of PT.XYZ, they still use manual attendance system for presence of computer laboratory assistant, so there are several problem like productivity decreases due to fraud in attendance, namely the help of friends to be absent without having to be present, to data errors. Through wireless fidelity programmers solve problems with prototype research models and Object Oriented Programming (OOP) methods. The software development tool is the Unified Modeling Language (UML). The Applications has made using hash function of encryption on admin passwords and the user passwords. Both of the encryptions work on private passwords, even the admin and programmers don't know the contents of the user's password. The main result of this research is we can provide that there’s many way to make presence system one of them uses WIFI.